On the question of the sources of forensic and tactical techniques - Shabanov, Vyacheslav B.; Krasikau, Uladzimir S. (Journal of the Belarusian State University. Law, 2024)
The authors of the article examine the positions of forensic scientists regarding such a criminalistic category as the source of a forensic and tactical techniques about which there is no unity in understanding of its essence, meaning and role in the scientific community. The opinions of the specialists regarding this subject of research are analysed. The authors’ vision of the source of criminalistic and tactical techniques in criminalistic (operational-investigative) tactics as forming the theoretical, practical basis of organisational and intellectual activity of a law enforcement officer and a judge is proposed.
Keywords: forensic and operational investigative tactics; forensic technique; source of forensic and tactical techniques